Overview of syntheses and molecular-design strategies for tetrazine-based fluorogenic probes - Choi, Sang Kee; Kim, Jonghoon; Kim, Eunha (Molecules, 2021)
Various bioorthogonal chemistries have been used for fluorescent imaging owing to the advantageous reactions they employ. Recent advances in bioorthogonal chemistry have revolu-tionized labeling strategies for fluorescence imaging, with inverse electron demand Diels–Alder (iEDDA) reactions in particular attracting recent attention owing to their fast kinetics and excellent specificity. One of the most interesting features of the iEDDA labeling strategy is that tetrazine-functionalized dyes are known to act as fluorogenic probes. In this review, we will focus on the synthesis, molecular-design strategies, and bioimaging applications of tetrazine-functionalized fluo-rogenic probes. Traditional Pinner reaction and “Pinner-like” reactions for tetrazine synthesis are discussed here, as well as metal-catalyzed C–C bond formations with convenient tetrazine intermedi-ates and the fabrication of tetrazine-conjugated fluorophores. In addition, four different quenching mechanisms for tetrazine-modified fluorophores are presented.
Keywords: Fluorescence; Fluorescent Dyes; Heterocyclic Compounds, 1-Ring; Kinetics; Optical Imaging; Bioimaging; Click chemistry; Fluorogenic; Tetrazine